CHOICE OF TECHNOLOGICAL PARAMETERS FOR PRODUCTION OF WIRE FOR ONBOARD RINGS WITH HEIGHTENED REQUIREMENTS TO ADHESION - A. V. Demidov; S. L. Bobrovnik; E. S. Seryogina; T. V. Martynyuk (Литьë и металлургия)
The work on choice of the production technology of wire for bead rings of tires with diameter of 12,6 mm providing fulfilment of the customer requirements on size of adhesion and residual covering by rubber is carried out.